Perception and determinants leading to antimicrobial (mis)use: A knowledge, attitude, and practices study in the rural communities of Odisha, India - Pattnaik, Matrujyoti; Nayak, Ashish Kumar; Karna, Sonam; Sahoo, Subrat Kumar; Palo, Subrata Kumar; Kanungo, Srikanta; Kshatri, Jaya Singh; Parai, Debaprasad; Walia, Kamini; Singh, Taru; Choudhary, Hari Ram; Pati, Sanghamitra; et al. (Frontiers in Public Health, 2023)
Antimicrobial resistance (AMR) has emerged as one of the major public health issues globally. This cross-sectional study determined knowledge, attitudes and practices (KAP) regarding antimicrobial use and AMR among rural communities of Tigiria (Odisha), India. A semi-structured questionnaire based on socio-demographic characteristics, antibiotics usage, awareness of antimicrobial resistance, healthcare utilization and quality of life were asked to the participants using an electronic device with Open Data Kit. Descriptive statistics, independent t-test and ANOVA were performed to analyze the variables. A total of 1003 participants were surveyed in the study from 25 villages of Tigiria. About 44.47% (95% CI: 41.36 - 47.60) of study participants have heard about antimicrobial medicines and 14.75% (95% CI: 12.65 – 17.13) of participants were involved in buying antibiotics without prescription over the counter. Around 20.14% (95% CI: 17.72 – 22.78) of participants, stopped taking antibiotics before completing the full course. The physical domain was the most affected with low scores compared to other domains of quality of life (QOL). The QOL scores were found significant (p-value <0.05) across age, gender, education and ethnicity. The study documented a significant level of KAP regarding antimicrobial (mis)use in the study. It is essential that antimicrobial stewardship programs for various stakeholders and educational programmes must be initiated to increase awareness of people on antimicrobial resistance.